Banking Merger, Challenges & Its Impact on the Financial Performance of Sudanese Banks: Empirical Study - Blue Nile Mashreq Bank (2015-2020) - El-Tahir, Omer Ali Babiker (Journal of Economic, Administrative and Legal Sciences, 2024)
The study has focused on Banking Merger in Sudan to reform Bank Sector as an objective, challenges, and its impact on Banking Performance. It has selected the experience of the Banks Merger between Blue Nile Bank and Mashreq Bank in October 2003 to understand the impacts and the results of this process on the Financial Performance (2015-2020).The main objective of the study is to analysis the impact of merger on the financial performance of commercial banks in Sudan and to know the concept of the banking merger in Sudan, the challenges and problems facing the banking merger in Sudan and Highlighting the impact of the experience of the Blue Nile Bank as a study of the situation of the merger of banking in Sudan on the level of financial performance.It has many findings like merger has led to implementing a good Capital Adequacy ratio also We find that the banking merger has succeeded in a great way in the Mashreq Blue Nile Bank, through the ability of the new bank to increase the capital, its assets, and annual profits after the merger until now and its impact on the financial performance of Sudanese banks.This study methodology follows the historical descriptive method to clarify the aspects related to banking mergers and to follow previous studies and the analytical method by taking the experience of the Blue Nile Mashreq Bank It has some recommendations like, the most important those Sudanese banks to take banking merger as a strategic option to create banking entities capable of global competition also it is necessary to activate the banking merger process more among Sudanese banks to avoid problems and obstacles facing the banking business.
Keywords: Banking Performance; Challenges; Banking Merger; Banking Sector Reform; Banking Entities